Obesity under affluence varies by welfare regimes: The effect of fast food, insecurity, and inequality. - Offer, A; Pechey, R; Ulijaszek, S (Nuffield College (University of Oxford), 2010)
Among affluent countries, those with market-liberal welfare regimes (which are also English-speaking) tend to have the highest prevalence of obesity. The impact of cheap, accessible high-energy food is often invoked in explanation. An alternative approach is that overeating is a response to stress, and that competition, uncertainty and inequality make market-liberal societies more stressful. This ecological regression meta-study pools 96 body-weight surveys from 11 countries c. 1994-2004. The fast-food ‘shock’ impact is found to work most strongly in market liberal countries. Economic insecurity, measured in several different ways, was almost twice as powerful, while the impact of inequality was weak, and went in the opposite direction.